Identification of Heterotic Crosses for yield and Water Use Efficiency Traits in Relation to Moisture Stress Tolerance in Groundnut (Arachis hypogaea L.) - John, K.; Reddy, P. Raghava; Naidu, T. C. M.; Naidu, N. V. (International Journal of Bio-resource and Stress Management, 2018)
The experimental material comprised of 24 F1 crosses generated through Line×Tester analysis. The relative heterosis, heterobeltiosis and standard heterosis were estimated for yield and water use efficiency traits. The heterobeltiosis for SPAD chlorophyll meter reading ranged from -20.45% (K-6×ICGV-91114) to 15.25% (TAG-24×TMV-2). For specific leaf area the heterobeltiosis ranged from 41.46% (TAG-24×ICGV-91114) to 17.03% (Rohini×Dharani). The cross Prasuna×TCGS -1416 recorded the highest heterobeltiosis for number of mature pods per plant (53.33%), Rohini×ICGV-91114 for shelling per cent (8.58%), Prasuna×Dharani for sound mature kernel per cent (10.04%), TAG-24×Dharani for kernel yield plant-1 (90.75%) and Prasuna×TCGS-1416 for pod yield plant-1 (60.69%). Based on heterobeltiosis the best heterotic crosses were identified for different traits viz., SPAD chlorophyll meter reading (TAG-24×TMV-2, K-6×TMV-2 and Greeshma x TMV-2), specific leaf area (TAG-24×ICGV-91114, K-6×TMV-2 and Greeshma×TCGS-1416), shelling per cent (Rohini x ICGV-91114, K-6×TCGS-1416 and TAG-24×Dharani), kernel yield plant-1 (TAG-24×Dharani, Greeshma×Dharani and Greeshma×TMV-2) and pod yield plant-1 (Prasuna×TCGS-1416, TAG-24×Dharani and Prasuna×ICGV-91114). These hybrids offer best possibilities of future exploitation for development of high yielding moisture stress tolerant groundnut genotypes.